Implementasi Pembelajaran Dalam Masa Pandemi Covid-19 Pada Guru Sekolah Dasar - Sejati, Amelia Wahyu; Muhroji; Rosyadi, Ajib; Wulandari, Desi Tri; Hidayat, Muhamad Taufik (Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study was to determine the implementation of online learning during the pandemic in spiritual, affective and psychomotor aspects. The type of research used in this study is a qualitative research, with a descriptive design. The data obtained by the researcher is data in the form of primary and secondary data with data collection techniques in the form of interviews and observations to 6 public and private elementary school teachers who are divided into low grade and high grade teachers in Rembang, Pati, Purwodadi, Sragen, and Madya Districts. Surakarta. The data analysis techniques used are 1) Data collection, 2) Data reduction, 3) Data presentation, and 4) Conclusions, the validity of the data using triangulation methods with research results as follows: 1) Implementation of online learning in the spiritual realm based on the results of the above interview can it can be concluded that the achievement of online learning in the spiritual realm runs optimally, 2) the implementation of online learning in the realm of attitudes based on the results of the interview above, it can be concluded that the achievement of online learning in the realm of attitudes runs optimally, and 3) the implementation of online learning in the realm of skills based on the results of interviews can it can be concluded that the achievement of online learning in the realm of skills received by students has maximum results. It can be concluded that the implementation of learning during the COVID-19 pandemic for elementary school teachers with maximum achievements.